Chapter Digital.VET : An innovative approach for teaching and training - Santarcangelo, Maria (Proceedings e report, 2023)
VET (Vocational Education and Training) Reforms and Labour Market reforms have started a process aimed at filling the gap between demand and supply of competences. The demand of competences, in fact, is affected by factors requiring the constant adjustment of production and training processes as well as the greater connection between education/training system and enterprises. Digital training, included in National Programmes of ERASMUS+, is essential in order to ensure effective training practices for the current VET system which is undergoing organizational and methodological change. In this context, Digital Teaching in VET System is an innovative approach to support the objectives set out in national and European strategies for applying ICT to VET systems through teachers/trainers training. The use of Augmented Reality, Virtual Reality and Mixed Reality technologies is an important strategy to innovate teaching and improve attention of students during the training session. iDid, application for immersive teaching, represent the deliverable of the project that allows VET teachers and trainers to produce contents of lessons using the potentialities of AR/VR/MR streams, and to share contents in a community oriented approach to transfer know-how and also obtain important user feedbacks.